오키나와 자립론의 한 사례: 류큐공화사회헌법C사(시)안을 중심으로 - 이지원; Chi Won Lee (한림일본학, 2015)
오키나와는 19세기 말 이후 일본제국, 미국 및 현대 일본 하에서 ‘식민지적 상황’에 놓여왔다. 이를 극복하려는 시도로 다양한 자립론이 분출되어 왔다. 가와미츠 신이치의 ‘류큐공화사회 헌법C사(시)안’(이하 헌법사안으로 약칭)은 그 중에서도 독특한 사례이다. 대부분의 자립론은 국가로서의 독립을 추구하거나, 일본 내에서 자치의 폭을 확대하는 것을 추구한다. 그러나 헌법사안은 국가를 철저히 부정하고 공화사회를 지향한다. 전쟁과 군대 보유에 반대하며, 침략을 당할 경우에도 방어적 무력조차 행사하지 않는 절대평화주의를 추구한다. 이러한 헌법사안의 내용은 너무 이상적이어서 현실성이 결여된 발상으로 비치기도 한다. 이 글에서는 이러한 유토피아적 헌법사안의 출현 배경과 현실성 및 현재적 의의에 대해 검토하였다. 헌법사안의 국가 부정 및 절대평화주의는 매우 공상적이나, 수백년 이상 지속된 오키나와의 ‘비무장’의 전통 및 강대국 사이에 위치한 지정학적 현실이라는 면에서 실은 적지 않은 현실성을 지닌다. 또한 일본의 헌법개정국면에서 ‘호헌론’을 넘어서는 ‘창헌론’의 구체적 사례를 보여준다는 점에서 현재적 의의를 지닌다. 이러한 발상은 ‘쿠로시오 로드 평화헌법’ 구상 및 아시아공동체 구상으로 확장되면서, 해양세력 및 대륙세력의 긴장 및 갈등 속에 위치한 한반도에도 시사하는 바가 크다. Okinawa has been subject to “colonial dominance" of imperialist Japan, the United States, and modern Japan since the late 19th century, and accordingly, there have been attempts to overcome this situation in various forms of theories of self-reliance. Among such efforts is the “Draft C of the Constitution of Ryukyu Republican Community" (hereafter referred to as “Draft C") written by Kawamitsu Shinichi. Most theories of self-reliance pursue independence as a nation state or greater autonomy within Japan. "Draft C," however, is a peculiar case in that it completely rejects the idea of a nation; instead, it seeks to build a republican community. It also pursues absolute pacifism that is opposed to war and the use of military force even in self-defense. Many have found these ideas posited”Draft C" too ideal and utopian and thus criticized them for being unpractical. This essay examines the background of this draft of constitution and speculates on its significance in our present age. Although the rejection of a nation and absolute pacifism in this draft may sound too unrealistic, these ideas actually have some solid foundation considering the tradition of "demilitarization" in Okinawa that has been continuing for hundreds of years as well as its geographical location among powerful nations. "Draft C" also holds great significance in our present age as it serves as aspecific example of a case of “new framing of a constitution” that goes beyond “protection of the constitution” in terms of constitutional amendments in Japan. And this idea was developed into “the Kuroshio road demilitarized zone” and “the East Asian Community” Initiative, and then it also provides significant implications for the situation of the Korean peninsula in the middle of conflicts between Superpowers.